The Relationship Between Individual Characteristics and Work Unit Factors With Patient Safety Culture at Regional Hospital X, Tanjung Jabung Timur Regency - Yansyah, Noveri; Guspianto, Guspianto; Noerjoedianto, Dwi; Amir, Andy; Asparian, Asparian; Kalsum, Ummi; Eka Rini, Willia Novita (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Patient Safety Culture (PSC) remains critically low at Regional General Hospital X, Tanjung Jabung Timur Regency, necessitating a systematic investigation of its determinants. Objective: This study aims to analyze the relationship between demographic characteristics and work unit factors and patient safety culture at Regional General Hospital X, Tanjung Jabung Timur Regency, in 2025. Method: Proportional random sampling was employed, and data were collected using the standardized Hospital Survey on Patient Safety Culture (HSOPSC) questionnaire. Bivariate analysis identified significant associations between PSC and several variables, including gender, education, employment status, work area, and workload. Multivariate logistic regression confirmed that work unit factors constituted the most dominant predictor of PSC Results and discussion: These findings indicate that PSC improvement requires targeted organizational interventions — particularly in workload management, interprofessional communication, and teamwork — rather than approaches focused solely on individual characteristics Conclusion: This study found that demographic characteristics and work unit factors have a significant relationship with patient safety culture at Regional General Hospital X, East Tanjung Jabung Regency. Therefore, efforts are needed to improve patient safety culture by strengthening work unit management, improving communication, teamwork, and optimal workload management to support the quality and safety of healthcare services in the hospital